Cutibacterium acnes of single locus sequence type clade C strains exhibit low susceptibility to benzoyl peroxide - Natsumi Sakaguchi; Shoji Seyama; Ryota Oba; Nobukazu Hayashi; Hidemasa Nakaminami (Journal of Global Antimicrobial Resistance, 2025)
Background: Cutibacterium acnes plays an important role in acne pathogenesis. Benzoyl peroxide (BPO) exhibits antimicrobial activity against C. acnes. We previously found that no clade C strains, as determined by single locus sequence typing (SLST), were found before the introduction of BPO in Japan. However, the prevalence of clade C strains increased after its introduction. In this study, we evaluated the susceptibility of C. acnes strains, belonging to different SLST clades, to BPO. Methods: Forty clinical C. acnes isolates from four distinct SLST clades obtained from acne lesions were analyzed. The susceptibility of C. acnes isolates to BPO was evaluated using a time-kill kinetic assay. Results: C. acnes clade C strains were less susceptible to BPO. In addition, the bactericidal effect of BPO was time-dependent across all clade strains. Conclusions: An increase in C. acnes clade C strains may diminish the efficacy of acne treatment. Therefore, the trends in the prevalence of C. acnes clade C strains should be monitored.